Low-dielectric heat-conducting gasket and preparation method thereof

By using a combination of aqueous acrylic acid and modified thermal conductivity filler, the problems of silicone oil leakage and high dielectric constant in electronic equipment are solved, and the preparation of low dielectric thermal conductivity is realized, with high thermal conductivity and good insulation resistance, and is suitable for applications with small gaps.

CN119505070AInactive Publication Date: 2025-02-25NINGBO JULI NEW MATERIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510083352.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing thermally conductive materials are used in electronic equipment, low molecules of silicone oil will exude, resulting in irreversible equipment damage. At the same time, ultra-thin thermally conductive gaskets are difficult to reach a thickness of 0.3mm, which cannot meet the requirements of small gaps and has a high dielectric constant, which affects the application.

Method used

Water-based acrylic acid and modified thermal fillers are used to prepare low-dielectric thermal conductivity gaskets through specific preparation processes and combined proportions, avoiding the problem of silicone oil leakage, and improving thermal conductivity and insulation resistance.

Benefits of technology

The dielectric constant is lower than 4.0 under the same thermal conductivity coefficient, which can meet the requirements of smaller gaps and avoid equipment damage caused by silicone oil leakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting gaskets, in particular to a low-dielectric heat-conducting gasket and a preparation method thereof.The low-dielectric heat-conducting gasket is prepared from, by weight, 10%-30% of waterborne acrylic acid, 60%-90% of modified heat-conducting filler, 0.5%-1.0% of fumed silica, 0.01%-0.05% of an antioxidant, 0.01%-0.05% of a flatting agent, 0.01%-0.05% of a dispersing agent, 0.01%-0.05% of a defoaming agent and 0.01%-0.1% of a curing agent; the viscosity of the water-based acrylic acid at 25 DEG C is 1000 to 5000 mPa.s. The low-dielectric heat-conducting gasket provided by the invention has the advantages that the heat conduction is obviously improved, the dielectric constant is less than 4.0, the density is less than 2.2 g / cc, the thickness can be within 0.3 mm, the appearance is free of needle holes, the light-weight development requirements of the automobile industry and the electronic industry are met, and the requirement of small-gap caulking can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermally conductive gaskets, and in particular to a low-dielectric thermally conductive gasket and a preparation method thereof. Background Art

[0002] With the development of the automotive and electronics industries, electronic components are becoming more and more sophisticated, dense, lightweight and miniaturized, which not only makes the heat generated by the equipment increase during operation, but also requires thermal conductive materials to have higher thermal conductivity, no silicone oil precipitation, and also requires thermal conductive materials to meet good low dielectric and ultra-thin filling properties.

[0003] Most of the existing thermal conductive materials are silicone system materials. Although silicone thermal conductive materials have the characteristics of high thermal conductivity, low stress, low thermal resistance, and high insulation, when they are placed in electronic equipment for use, the low molecular weight silicone oil in the silicone thermal conductive material will seep out due to heat and extrusion of components, and the volatiles in the silicone oil will also cause irreversible damage to the equipment.

[0004] Although acrylic thermal pads have been studied, they are mainly based on oily acrylic acid and use UV technology. For example, Chinese patent CN119019997A discloses a thermal pad and its preparation method, and an electronic component. The preparation method of the thermal pad includes mixing raw materials including a UV curing composition and a thermally conductive powder to obtain a thermally conductive colloid, and vacuuming and degassing the thermally conductive colloid, rolling it into sheets, and UV curing it in turn to obtain a thermally conductive pad. UV light is harmful to the human body. In addition, it is difficult to make ultra-thin thermal pads with a thickness of 0.3mm, which is difficult to meet the requirements of filling small gaps, and the high dielectric constant affects its application. At present, ultra-thin silicon-free high thermal conductive pads are still relatively blank. If the above problems can be solved, the application of silicon-free thermal conductive materials will be more extensive. Summary of the invention

[0005] In order to solve the problems in the prior art, the first aspect of the present invention provides a low dielectric thermal conductive gasket. The preparation raw materials include, by weight percentage, 10-35% water-based acrylic acid, 60-89% modified thermal conductive filler, 0.5-5% fumed silica, 0.01-0.1% antioxidant, 0.01-0.1% leveling agent, 0.01-0.1% dispersant, 0.01-0.1% defoaming agent, and 0.01-0.1% curing agent; the viscosity of the water-based acrylic acid at 25°C is 1000-5000mPa·s.

[0006] In one embodiment, the aqueous acrylic acid has a viscosity of any one of 1000 mPa·s, 2000 mPa·s, 3000 mPa·s, 4000 mPa·s, and 5000 mPa·s at 25°C.

[0007] In a preferred embodiment, the viscosity of the aqueous acrylic acid is 2000 mPa·s.

[0008] In one embodiment, the raw materials for preparing the water-based acrylic acid include, by weight percentage, 30-40% acrylic acid monomer, 0.01-1% thermal initiator, 20-30% n-butanol, 0.1-1% pH adjuster, and the balance is made up of solvent.

[0009] In one embodiment, the acrylic monomer includes at least one of a monofunctional alkyl acrylate, a monofunctional acryl monomer, and a monofunctional acrylic vinyl ether monomer.

[0010] In one embodiment, the monofunctional alkyl acrylate includes at least one of methyl methacrylate, ethyl acrylate, hydroxyethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, n-heptyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, isononyl acrylate, n-decyl acrylate, isodecyl acrylate, n-dodecyl acrylate, isomyristyl acrylate, n-tridecyl acrylate, n-tetradecyl acrylate, n-stearyl acrylate, isostearyl acrylate, and n-lauryl acrylate.

[0011] In one embodiment, the monofunctional acrylic vinyl ether-based monomer includes at least one of 2-(2-vinyloxyethoxy)ethyl acrylate, 2-vinyloxyethyl acrylate, 3-vinyloxyethyl acrylate, 2-vinyloxypropyl acrylate, 1-methyl-2-vinyloxyethyl acrylate, 4-vinyloxybutyl acrylate, 6-vinyloxyhexyl acrylate, 4-vinyloxycyclohexyl acrylate, 4-vinyloxymethylcyclohexylmethyl acrylate, 2-(2-vinyloxyisopropoxy)propyl acrylate, and 2-{2-(2-vinyloxyethoxy)ethoxy}ethyl acrylate.

[0012] In one embodiment, the monofunctional acrylic monomer includes an acrylic ester monomer, which may be exemplified by methyl acrylate, ethyl acrylate, and butyl acrylate.

[0013] In a preferred embodiment, the acrylic monomer is a monofunctional alkyl acrylate.

[0014] In a preferred embodiment, the monofunctional alkyl acrylate is methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate and n-dodecyl acrylate.

[0015] In one embodiment, the mass ratio of methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate and n-dodecyl acrylate is (1-2): (3-4): (4-5): (3-4).

[0016] In a preferred embodiment, the mass ratio of methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate and n-dodecyl acrylate is 2:3:4:3.

[0017] In one embodiment, the thermal initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide, and tert-butyl hydroperoxide.

[0018] In a preferred embodiment, the thermal initiator is benzoyl peroxide.

[0019] In one embodiment, the solvent is water.

[0020] In one embodiment, the pH adjuster is aqueous ammonia.

[0021] In a preferred embodiment, the mass fraction of ammonia in the ammonia water is 30%.

[0022] In one embodiment, the method for preparing water-based acrylic acid comprises at least the following steps: S1, mixing acrylic acid monomer and thermal initiator to obtain component A; S2, adding n-butanol into a three-necked flask, stirring and heating to 100-120°C, adding component A dropwise while maintaining constant temperature, and after complete addition, continue the constant temperature reaction for 4-5h, cool down to 70-80°C, and perform vacuum distillation to obtain a viscous liquid; S3. Add a solvent to dilute the viscous liquid at 70-80° C., adjust the pH value to 7.0-7.5 with a pH adjuster, and add 1.0 kg of solvent to obtain the product.

[0023] In one embodiment, the stirring rate in step S1 is 300-400 rpm / min, and the stirring time is 10-20 min.

[0024] In a preferred embodiment, the stirring rate in step S1 is 300 rpm / min, and the stirring time is 10 min.

[0025] In one embodiment, the stirring rate in step S2 is 300-400 rpm / min, which can be 300 rpm / min, 350 rpm / min, or 400 rpm / min.

[0026] In one embodiment, the constant temperature dripping time in step S2 is 4-5 hours, which can be 4 hours, 4.5 hours, or 5 hours.

[0027] In a preferred embodiment, the S2 step is specifically as follows: n-butanol is added into a three-necked flask, stirred at a rate of 300 rpm / min, and the temperature is raised to 110° C., component A is added dropwise while maintaining a constant temperature, and after the addition for 4 hours, the constant temperature reaction is continued for 4 hours, the temperature is lowered to 75° C., and reduced pressure distillation is performed to obtain a viscous liquid.

[0028] In one embodiment, the copolymer monomer content in the viscous liquid is greater than 90.0 wt %.

[0029] In one embodiment, the step S3 is specifically as follows: adding a solvent to dilute the viscous liquid at 75° C., adjusting the pH value to 7.2 with a pH adjuster, and supplementing 1.0 kg of solvent to obtain the product.

[0030] In one embodiment, the modified thermally conductive filler includes at least two modified thermally conductive fillers with different average particle sizes; the average particle size D50 of the modified thermally conductive filler is 2-90 μm, which can be 2 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 75 μm, 80 μm, and 90 μm.

[0031] In a preferred embodiment, the modified thermally conductive filler is a combination of three modified thermally conductive fillers with different average particle sizes.

[0032] In one embodiment, the average particle sizes D50 of the three modified thermally conductive fillers with different average particle sizes are 5 μm, 40 μm, and 75 μm.

[0033] In a preferred embodiment, the mass ratio of the three modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 40 μm: D50 of 75 μm=2:3:3.

[0034] In one embodiment, the raw materials for preparing the modified thermally conductive filler include: a thermally conductive filler, a surface modifier, anhydrous ethanol and water; the mass of the surface modifier is 0.1-1wt% of the mass of the thermally conductive filler, which can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt% and 1wt%.

[0035] In one embodiment, the surface modifier includes at least one of a silane coupling agent, a titanate coupling agent, and an aluminate coupling agent.

[0036] In one embodiment, the silane coupling agent includes any one of 3-aminopropylethoxysiloxane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, dodecyltrimethoxysilane, and vinyltriethoxysilane.

[0037] In one embodiment, the thermally conductive filler includes at least one of aluminum hydroxide, boron nitride, aluminum nitride, aluminum silicate, and aluminum oxide.

[0038] In a preferred embodiment, the thermally conductive filler is boron nitride.

[0039] In one embodiment, the preparation method of the modified thermally conductive filler includes at least the following steps: mixing the thermally conductive filler, the surface modifier, anhydrous ethanol and water at 25°C to obtain a mixture A, and stirring the mixture A at 140-160°C to obtain the modified thermally conductive filler.

[0040] In one embodiment, the mixing and stirring has a stirring rate of 100-200 rpm / min and a stirring time of 40-60 min.

[0041] In one embodiment, the stirring reaction rate is 30-50 rpm / min, and the stirring time is 40-60 min.

[0042] In a preferred embodiment, the preparation method of the modified thermally conductive filler includes at least the following steps: mixing the thermally conductive filler, the surface modifier, anhydrous ethanol and water at 25°C, a stirring rate of 100 rpm / min, and a stirring time of 50 min to obtain a mixture A; stirring the mixture A at 150°C and 40 rpm / min for 50 min to obtain the modified thermally conductive filler.

[0043] In one embodiment, the antioxidant includes any one of a peroxide decomposition antioxidant, a free radical scavenging antioxidant, and a metal deactivation antioxidant, which can be exemplified by zinc dialkyl dithiophosphate, zinc dialkyl dithiocarbamate, N-phenyl-α-naphthylamine, alkyl phenothiazine, benzotriazole derivatives, and mercaptobenzothiazole derivatives.

[0044] In a preferred embodiment, the antioxidant is IRGANOX 1010, purchased from BASF AG.

[0045] In one embodiment, the leveling agent includes at least one of silicone oil, polydimethylsiloxane, polyether polyester modified organic siloxane, terminal modified organic silicon, acrylic leveling agent, and fluorine leveling agent.

[0046] In a preferred embodiment, the leveling agent is an acrylic leveling agent.

[0047] In a more preferred embodiment, the acrylic leveling agent has a brand number of 1153 and is purchased from Shenzhen Moen Chemical Co., Ltd.

[0048] In one embodiment, the dispersant includes at least one of a fatty acid dispersant, an aliphatic amide dispersant, an ester dispersant, a paraffin dispersant, a metal soap dispersant, and a low molecular weight wax dispersant.

[0049] In a preferred embodiment, the brand of the dispersant is TEGODispers 685, which is purchased from Evonik Degussa Digo Additives.

[0050] In one embodiment, the defoaming agent includes at least one of an alcohol defoaming agent, a fatty acid defoaming agent, a fatty acid ester defoaming agent, a phosphate ester defoaming agent, a mineral oil defoaming agent, and an amide defoaming agent.

[0051] In a preferred embodiment, the defoaming agent is of BYK-011, purchased from BYK Chemical Co., Ltd.

[0052] In one embodiment, the curing agent includes at least one of an acid catalyst, an isocyanate, and an aziridine crosslinking agent.

[0053] In a preferred embodiment, the curing agent is isocyanate with a brand name of MDI-50, which is purchased from BASF AG.

[0054] A second aspect of the present invention provides a method for preparing a low dielectric thermal conductive gasket, comprising at least the following steps: The water-based acrylic acid, the modified thermal conductive filler, the fumed silica, the leveling agent, the dispersant, the defoaming agent and the curing agent are uniformly stirred and then subjected to vacuum degassing treatment to obtain a thermal conductive adhesive; The thermal conductive adhesive is treated at 70-80° C. for 20-30 minutes, coated with a heating roller and calendered to obtain the thermal conductive adhesive.

[0055] In one embodiment, the stirring conditions are: a stirring rate of 60-100 rpm / min, and a stirring time of 30-50 min.

[0056] In a preferred embodiment, the stirring conditions are: a stirring rate of 80 rpm / min and a stirring time of 40 min.

[0057] In one embodiment, the vacuum degassing method includes vacuum vibration degassing.

[0058] In one embodiment, the vacuum degassing conditions are: relative vacuum pressure of -0.1-0.08 MPa, and degassing time of 10-20 min.

[0059] In a preferred embodiment, the vacuum degassing conditions are: relative vacuum pressure is 0.05 MPa, and the degassing time is 15 min.

[0060] In one embodiment, the temperature of the heating roller calendering is 120-140°C, which may be 120°C, 130°C, or 140°C.

[0061] In a preferred embodiment, the temperature of the heating roller calendering is 130°C.

[0062] Beneficial Effects 1. This application uses homemade water-based acrylic acid, especially controlling the acrylic acid monomer to be a compound of methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate, and n-dodecyl acrylate. The prepared silicone-free thermal conductive gasket has a lower dielectric constant of <4.0 compared to other thermal conductive gaskets at the same thermal conductivity.

[0063] 2. The present application adopts a self-made modified thermally conductive filler, especially a combination of modified thermally conductive fillers with three different average particle sizes. When the D50 of the modified thermally conductive fillers with three different average particle sizes is 5μm, 40μm, and 75μm, the prepared silicone-free thermally conductive gasket has high thermal conductivity and good insulation resistance. The density of the silicone-free gasket is low, <2.2g / cc, which meets the lightweight development needs of the automotive and electronics industries.

[0064] 3. This application avoids the influence of bubbles generated after cross-linking of the silicone-free thermal conductive gasket on the thermal conductivity and other properties of the product by controlling the viscosity of the cyclic water-based acrylate and adopting a specific preparation process.

[0065] 4. The low dielectric thermal conductive gasket prepared in the present application is a silicon-free thermal conductive gasket, which can avoid the problem that low molecules in the silicone oil of conventional organic silicon thermal conductive materials will seep out due to heat and extrusion of parts.

[0066] 5. The low-dielectric silicone-free thermally conductive gasket prepared in this application can have a thickness of less than 0.3 mm and has no pinholes in appearance, which can meet the requirements of filling smaller gaps. DETAILED DESCRIPTION

[0067] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. The experimental methods in the examples without specifying specific conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0068] Example 1 In a first aspect, the present embodiment provides a low dielectric thermal conductive gasket, wherein the raw materials for preparing the gasket include 100 g of water-based acrylic acid, 800 g of modified thermal conductive filler, 6 g of fumed silica, 0.1 g of antioxidant, 0.2 g of leveling agent, 0.1 g of dispersant, 0.15 g of defoaming agent, and 0.2 g of curing agent; the viscosity of the water-based acrylic acid at 25°C is 1000 mPa·s.

[0069] The raw materials for preparing the water-based acrylic acid include, by weight percentage, 1200 g of acrylic acid monomer, 2.3 g of thermal initiator, 800 g of n-butanol, 5 g of pH regulator, and 1000 g of solvent.

[0070] The acrylic monomers are methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate, and n-dodecyl acrylate. The mass ratio of methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate, and n-dodecyl acrylate is 2:3:4:3.

[0071] The thermal initiator is benzoyl peroxide.

[0072] The solvent is water. The pH regulator is ammonia water, and the mass fraction of ammonia in the ammonia water is 30%.

[0073] The preparation method of the water-based acrylic acid comprises the following steps: S1. Stir the acrylic acid monomer and the thermal initiator to obtain component A at a stirring rate of 300 rpm / min for 10 min. S2, adding n-butanol into a three-necked flask, stirring at a rate of 300 rpm / min, heating to 110° C., adding component A dropwise while maintaining the constant temperature, continuing the constant temperature reaction for 4 hours, cooling to 75° C., and performing reduced pressure distillation to obtain a viscous liquid, wherein the copolymer monomer content in the viscous liquid is greater than 90.0wt%; S3. Add a solvent to dilute the viscous liquid at 75° C., adjust the pH value to 7.2 with a pH adjuster, and add 1.0 kg of solvent to obtain the product.

[0074] The modified thermally conductive filler is a combination of three modified thermally conductive fillers with different average particle sizes. The average particle sizes D50 of the three modified thermally conductive fillers with different average particle sizes are 5 μm, 40 μm, and 75 μm.

[0075] The mass ratio of the three modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 40 μm: D50 of 75 μm=2:3:3.

[0076] The raw materials for preparing the modified thermally conductive filler include: 1000 g of thermally conductive filler, 25 g of surface modifier, 200 g of anhydrous ethanol and 100 g of water.

[0077] The thermal conductive filler is boron nitride. The surface modifier is 3-aminopropylethoxysiloxane.

[0078] The preparation method of the modified thermally conductive filler comprises at least the following steps: mixing the thermally conductive filler, the surface modifier, anhydrous ethanol and water at 25° C., a stirring rate of 100 rpm / min and a stirring time of 50 min to obtain a mixture A; stirring the mixture A at 150° C. and 40 rpm / min for 50 min to obtain the modified thermally conductive filler.

[0079] The brand of the antioxidant is IRGANOX1010, purchased from BASF AG.

[0080] The leveling agent is an acrylic leveling agent. The brand of the acrylic leveling agent is 1153, purchased from Shenzhen Mo Neng Chemical Co., Ltd.

[0081] The brand of the dispersant is TEGODispers 685, which is purchased from Evonik Degussa Digo Additives.

[0082] The defoamer was BYK-011, purchased from BYK Chemical Co., Ltd.

[0083] The curing agent is isocyanate with a brand name of MDI-50, purchased from BASF AG.

[0084] A second aspect of the present embodiment provides a method for preparing a low dielectric thermal conductive gasket, comprising at least the following steps: Aqueous acrylic acid, modified thermal conductive filler, fumed silica, leveling agent, dispersant, defoamer and curing agent were stirred at a stirring rate of 80 rpm / min for 40 minutes and then subjected to vacuum degassing treatment to obtain a thermal conductive adhesive; The thermal conductive adhesive is treated at 70° C. for 20 minutes, coated with a heated roller and calendered to obtain the thermal conductive adhesive.

[0085] The vacuum degassing conditions are as follows: relative vacuum pressure is 0.05 MPa, degassing time is 15 min; and the temperature of the heating roller calendering is 130°C.

[0086] Example 2 The specific implementation of this embodiment is the same as that of Embodiment 1, except that the modified thermally conductive filler is a combination of two modified thermally conductive fillers with different average particle sizes, and the average particle sizes D50 of the two modified thermally conductive fillers with different average particle sizes are 5 μm and 75 μm.

[0087] The mass ratio of the two modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 75 μm=1:3.

[0088] Example 3 The specific implementation of this embodiment is the same as that of Embodiment 1, except that the modified thermally conductive filler is a combination of two modified thermally conductive fillers with different average particle sizes, and the average particle sizes D50 of the two modified thermally conductive fillers with different average particle sizes are 5 μm and 75 μm.

[0089] The mass ratio of the two modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 75 μm=2:3.

[0090] Example 4 The specific implementation of this embodiment is the same as that of Embodiment 1, except that the modified thermally conductive filler is a combination of three modified thermally conductive fillers with different average particle sizes, wherein the average particle sizes D50 of the three modified thermally conductive fillers with different average particle sizes are 5 μm, 40 μm, and 75 μm.

[0091] The mass ratio of the three modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 40 μm: D50 of 75 μm=3:7:6.

[0092] Comparative Example 1 The specific implementation method of this comparative example is the same as that of Example 1, except that, in the first aspect of this comparative example, a thermally conductive gasket is provided, and the raw materials for preparation include 100 g of oily acrylic acid, 700 g of modified thermally conductive filler, 6 g of fumed silica, 0.1 g of antioxidant, 0.2 g of leveling agent, 0.1 g of dispersant, 0.15 g of defoaming agent, and 0.2 g of curing agent; the viscosity of the oily acrylic acid at 25°C is 2000 mPa·s.

[0093] The brand of the oily acrylic acid is PSA-3300, which is purchased from Guangdong Bangku Chemical Technology Co., Ltd.

[0094] The thermally conductive filler is aluminum hydroxide.

[0095] Comparative Example 2 The specific implementation of this comparative example is the same as that of Example 1, except that in this comparative example, the water-based acrylic acid is replaced by an oily acrylic acid, wherein the oily acrylic acid has a viscosity of 2000 mPa·s at 25° C., a brand of PSA-3300, and is purchased from Guangdong Bangku Chemical Technology Co., Ltd.

[0096] The thermally conductive filler is aluminum hydroxide.

[0097] The modified thermally conductive filler is a combination of three modified thermally conductive fillers with different average particle sizes. The average particle sizes D50 of the three modified thermally conductive fillers with different average particle sizes are 5 μm, 40 μm, and 75 μm.

[0098] The mass ratio of the three modified thermally conductive fillers with different average particle sizes is D50 of 5 μm: D50 of 40 μm: D50 of 75 μm=2:3:2.

[0099] Comparative Example 3 The specific implementation method of this comparative example is the same as that of Example 1, except that, in the first aspect of this comparative example, a thermally conductive gasket is provided, and the raw materials for preparing the thermally conductive gasket include 100 g of oily acrylic acid, 800 g of modified thermally conductive filler, 6 g of fumed silica, 0.1 g of antioxidant, 0.2 g of leveling agent, 0.1 g of dispersant, and 0.2 g of curing agent; the viscosity of the oily acrylic acid at 25°C is 2000 mPa·s.

[0100] The brand of the oily acrylic acid is PSA-3300, which is purchased from Guangdong Bangku Chemical Technology Co., Ltd.

[0101] Comparative Example 4 The specific implementation method of this comparative example is the same as that of Example 1, except that, in the first aspect of this comparative example, a thermally conductive gasket is provided, and the raw materials for preparation include 100 g of oily acrylic acid, 800 g of modified thermally conductive filler, 6 g of fumed silica, 0.1 g of antioxidant, 0.2 g of leveling agent, 0.1 g of dispersant, 0.15 g of defoaming agent, and 0.1 g of curing agent; the viscosity of the oily acrylic acid at 25°C is 2000 mPa·s.

[0102] The brand of the oily acrylic acid is PSA-3300, which is purchased from Guangdong Bangku Chemical Technology Co., Ltd.

[0103] Comparative Example 5 The specific implementation method of this comparative example is the same as that of Example 1, except that, in the first aspect of this comparative example, a thermally conductive gasket is provided, and the raw materials for preparing the thermally conductive gasket include 100 g of oily acrylic acid, 800 g of modified thermally conductive filler, 6 g of fumed silica, 0.1 g of antioxidant, 0.2 g of leveling agent, 0.1 g of dispersant, 0.15 g of defoaming agent, and 0.4 g of curing agent; the viscosity of the oily acrylic acid at 25°C is 2000 mPa·s.

[0104] The brand of the oily acrylic acid is PSA-3300, which is purchased from Guangdong Bangku Chemical Technology Co., Ltd.

[0105] Performance Testing The following tests were performed on the thermally conductive pads prepared in each embodiment and comparative example: 1. Thermal conductivity is tested according to ISO 22007-2. 2. The dielectric constant is tested according to ASTM D150. 3. Density was tested according to ASTM D792. The test results are shown in Table 1.

[0106] Table 1

[0107] As can be seen from Table 1, the low dielectric silicone-free thermally conductive gasket provided by the present application can be less than 0.3 mm thick compared to other thermally conductive gaskets, and at the same thermal conductivity, the dielectric constant is lower than 4.0; it can improve the problems of low-cost electricity and ultra-thin gap filling during use.

Claims

1. A low dielectric thermal conductive gasket, characterized in that: The raw materials include, by weight percentage, 10-35% of water-based acrylic acid, 60-89% of modified thermal conductive filler, 0.5-5% of fumed silica, 0.01-0.1% of antioxidant, 0.01-0.1% of leveling agent, 0.01-0.1% of dispersant, 0.01-0.1% of defoaming agent, and 0.01-0.1% of curing agent; the viscosity of the water-based acrylic acid at 25° C. is 1000-5000 mPa·s.

2. The low dielectric thermal conductive gasket according to claim 1, characterized in that: The raw materials for preparing the water-based acrylic acid include, by weight percentage, 28-40% acrylic acid monomer, 0.01-1% thermal initiator, 20-30% n-butanol, 0.1-1% pH regulator, and the balance is made up of solvent.

3. The low dielectric thermal conductive gasket according to claim 2, characterized in that: The acrylic monomer includes at least one of a monofunctional alkyl acrylate, a monofunctional acryl monomer, and a monofunctional acrylic vinyl ether monomer.

4. The low dielectric thermal conductive gasket according to claim 3, characterized in that: The monofunctional alkyl acrylate includes at least one of methyl methacrylate, ethyl acrylate, hydroxyethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, tert-butyl acrylate, isobutyl acrylate, n-pentyl acrylate, isopentyl acrylate, n-hexyl acrylate, cyclohexyl acrylate, n-heptyl acrylate, n-octyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, n-nonyl acrylate, isononyl acrylate, n-decyl acrylate, isodecyl acrylate, n-dodecyl acrylate, isomyristyl acrylate, n-tridecyl acrylate, n-tetradecyl acrylate, n-stearyl acrylate, isostearyl acrylate, and n-lauryl acrylate.

5. The low dielectric thermal conductive gasket according to claim 4, characterized in that: The mass ratio of methyl methacrylate, hydroxyethyl acrylate, n-butyl acrylate and n-dodecyl acrylate is (1-2): (3-4): (4-5): (3-4).

6. The low dielectric thermal conductive gasket according to any one of claims 2 to 5, characterized in that: The preparation method of the water-based acrylic acid comprises at least the following steps: S1, mixing acrylic acid monomer and thermal initiator to obtain component A; S2, adding n-butanol into a three-necked flask, stirring and heating to 100-120°C, adding component A dropwise while maintaining constant temperature, and after complete addition, continue the constant temperature reaction for 4-5h, cool down to 70-80°C, and perform vacuum distillation to obtain a viscous liquid; S3, adding solvent to the viscous liquid at 70.0-80.0°C for dilution, adjusting the pH value to 7.0-7.5 with a pH adjuster, and adding 1 kg of solvent to obtain.

7. The low dielectric thermal conductive gasket according to claim 1, characterized in that: The modified thermally conductive filler comprises at least two modified thermally conductive fillers with different average particle sizes; the average particle size D50 of the modified thermally conductive filler is 2-90 μm.

8. The low dielectric thermal conductive gasket according to claim 7, characterized in that: The raw materials for preparing the modified thermally conductive filler include: a thermally conductive filler, a surface modifier, anhydrous ethanol and water; the mass of the surface modifier is 0.1-1wt% of the mass of the thermally conductive filler.

9. The low dielectric thermal conductive gasket according to claim 7 or 8, characterized in that: The preparation method of the modified thermally conductive filler comprises at least the following steps: mixing the thermally conductive filler, the surface modifier, anhydrous ethanol and water at 25° C. to obtain a mixture A, and stirring the mixture A at 140-160° C. to obtain the modified thermally conductive filler.

10. A method for preparing a low dielectric thermal conductive gasket according to any one of claims 1 to 9, characterized in that: At least the following steps are included: The water-based acrylic acid, the modified thermal conductive filler, the fumed silica, the leveling agent, the dispersant, the defoaming agent and the curing agent are uniformly stirred and then subjected to vacuum degassing treatment to obtain a thermal conductive adhesive; The thermal conductive adhesive is treated at 70-80° C. for 20-30 minutes, coated with a heating roller and calendered to obtain the thermal conductive adhesive.

Citation Information

Patent Citations

  • Heat-conducting gasket, preparation method thereof and electronic component

    CN119019997A

  • Acrylic heat-conducting gel as well as preparation method and application thereof

    CN117209939A

  • Thermocuring heat-conducting acrylate gasket and preparation method thereof

    CN117384603A

  • Silicon-free high-thermal-conductivity heat-conducting paste and preparation method thereof

    CN117487302A

  • Composition for Low Dielectric Thermally Conductive Material and Low Dielectric Thermally Conductive Material

    US20220017804A1